2019
DOI: 10.1007/s10826-019-01482-w
|View full text |Cite
|
Sign up to set email alerts
|

Health School-based Mindfulness Interventions for Improving Mental Health: A Systematic Review and Thematic Synthesis of Qualitative Studies

Abstract: Objectives School-based mindfulness interventions have recently shown promise for treating and preventing mental health issues in young people. However, the literature lacks a high-level perspective of the impact of mindfulness on young people's mental health according to their own first-hand accounts. Therefore, the objective of this study was to conduct the first systematic review and thematic synthesis to rigorously evaluate the qualitative evidence pertaining to students' experiences of school-based MBIs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 34 publications
4
35
0
Order By: Relevance
“…‘.b’, mindful schools, well and resilience program) have been implemented across the world. 79 , 80 These programmes can target at students, teachers, and even parents or caregivers. 81 Recent systematic reviews found MBIs hold promises in particular in improving resilience to stress, cognitive performance such as attention, and emotional problems in children and youths.…”
Section: Mindfulness In Different Settingsmentioning
confidence: 99%
“…‘.b’, mindful schools, well and resilience program) have been implemented across the world. 79 , 80 These programmes can target at students, teachers, and even parents or caregivers. 81 Recent systematic reviews found MBIs hold promises in particular in improving resilience to stress, cognitive performance such as attention, and emotional problems in children and youths.…”
Section: Mindfulness In Different Settingsmentioning
confidence: 99%
“…Inconsistency has been identified in terms of the experience of the teachers who deliver mindful parenting interventions (Sapthiang, Van Gordon & Shonin, 2019a, 2019bVan Gordon et al, 2019). For example, in some studies, the mindfulness teacher is not mentioned (Behbahani et al, 2018;Corthorn, 2018;May et al, 2016), and multiple studies reference "mental health professionals" conducting mindful parenting training following participation in an eight-day mindfulness training course Meppelink et al, 2016;Potharst et al, 2018).…”
Section: Key Implications For Practicementioning
confidence: 99%
“…Mindfulness also has applications in, for example, organizational settings (e.g., improving work-related well-being; Shonin, Van Gordon, Dunn, et al, 2014), forensic psychology (e.g., reducing reoffending; Auty et al, 2017), and educational psychology (e.g., enhancing learning environments; Sapthiang et al, 2019). Furthermore, neuroimaging studies indicate that mindfulness can augment self-regulatory efficacy; the most consistent longitudinal effect is increased insular cortex activity (Younga et al, 2018).…”
Section: Historymentioning
confidence: 99%